Integrative therapy for acute, subacute and chronic facial palsy: repeated differential facial nerve blocks combined with hypodermic needle-based facial nerve stimulation - Mun, Hah Yong; Sirh, So Woon; Sirh, Heon Man; Sirh, Soo Ji (Frontiers in Neurology, 2025)
IntroductionDespite various recommended treatments, no effective therapy has been established for the satisfactory rehabilitation of subacute and chronic debilitating facial palsy. To address this, we evaluated the safety and efficacy of a novel therapeutic approach that combines repeated differential facial nerve blocks with facial nerve stimulation using a hypodermic needle.MethodsWe retrospectively reviewed 47 patients (acute, n = 4; subacute, n = 3; chronic, n = 40) who were treated at a private pain clinic between January 2017 and December 2023. Patients with persistent facial palsy who were unresponsive to conventional therapies underwent repeated sessions of bilateral facial nerve block following hypodermic needle stimulation of the facial nerves and branches. Facial function was assessed using the House–Brackmann and Sunnybrook grading systems.ResultsMore than 85% of patients showed significant improvements in facial symmetry and function. In the chronic group, Sunnybrook scores improved from 42 to 78 (P < 0.01), and House-Brackmann grades improved from IV–V to I–II. In the acute and subacute groups, both grading scores showed significant improvement. Transient bruising was noted as a minor adverse event, and the clinical improvement remained stable after treatment.ConclusionsOur novel integrative treatment is demonstrated to be a safe and effective option for treating intractable subacute and chronic facial palsy.